Determination of octreotide acetate as radiosensitizer in breast cancer cell lines - Alkhansa, Salih Mahmoud Abdalla (2022)
Breast cancer is a common type of cancer that affects women worldwide and causes death related to cancer. Radiotherapy is one of the treatment options for breast cancer. Ionizing radiation (IR), like X-rays and gamma rays, are used for c Cancer treatment because they can penetrate soft tissue, bone vs soft tissue. The main problem in radiotherapy is most cancer cells are radio-resistant to treatment. Radiosensitizer agents combined with radiation therapy are more effective against radio-resistant cancer cells including breast cancer. In this study, octreotide acetate was used with an -radiation combination to investigate its role as a radiosensitizer in breast cancer cells. In this study the response of MCF7 and MDA-MB231 breast cancer cell lines to ionizing X-radiation was investigated. Somatostatin receptors (SSTRs1-5) measured in both MCF7 and MDA-MB231 cell lines. Furthermore, this study also evaluated the cytotoxicity of octreotide acetate and the effect of octreotide acetate alone and combined with X-radiation in MCF7 cells. Radiation response in both cell lines evaluated through ApoTox-Glo™ Triplex Assay to assess viability, cytotoxicity and apoptosis; as well as western blot assay for ƳH2AX and BAX measurements. The cytotoxicity of octreotide acetate was measured by Realtime-Glo™ MT Cell Viability Assay. Clonogenic assay was performed for cell survival and quantitative real -time polymerase chain reaction (qRT -PCR) assay used to determine the gene expression of SSTRs1-5, Nanog and BAX. Cell morphological changes were documented. The results revealed that MDA-MB231 cell line was sensitive to radiation at high dose of 8.5 Gy compared to unirradiated cells (P=0.002). While MCF7 cell line was resistant to radiation, there was no difference between the irradiated and non-irradiated cells, however, SSTR1, SSTR2, SSTR3 and SSTR4 mRNA expression were significantly higher in MDA-MB231 cell line as compared to MCF-7 cell line (P=0.02, 0.002, 0.001, 0.01) respectively. These findings showed that MCF7 is a radio- resistant cell line expressed low levels of SSTRs 1-5 which considered a suitable model for study the effects of octreotide acetate agonist as radiosensitizer in breast cancer. MCF7 treated with different concentration of octreotide acetate either alone or combined with X-radiation. 12.5μm of octreotide acetate combined with X-Ray showed statistically significant increased levels of SSTRs 1 to 4 compared to unirradiated cells among another treatment groups (P= 0.001). The synergism effect of octreotide acetate at concentrations of 12.5μm showed enhancement in radiosensitivity and induced apoptosis in MCF7 cell line. In conclusion, the results showed that octreotide acetate has a potential role as radiosensitizer agent in MCF7 breast cancer cell line.